ANALYSIS OF THE DEVELOPMENT OF TRANSIT TRAFFIC THROUGH THE CENTRAL ASIAN TRANSPORT CORRIDORS WITH THE PARTICIPATION OF UZBEK RAILWAYS - Mavluda Lutfullaevna Fayzikhodjaeva (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper makes analyses of the development of transit traffic through the Central Asian transport corridors with the participation of Uzbek railways. On this case, research has been conducted both methodologically and theoretically in order to get better development instrument as the whole. Finally, research has underlined major outcomes and shortcoming of the transit development in the Republic of Uzbekistan as the whole.